ANALISIS PELAKSANAAN PENILAIAN SIKAP KURIKULUM 2013 - Lahubu, Yessika Destiana; Marvida, Tria; Y Anuli, Wadan (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Attitude assessment is part of the actual teacher assessment to measure how well a student has achieved attitude skills. Attitude aspects are divided into two categories: spiritual and social attitudes. The 2013 curriculum uses observational, self-assessment, and peer assessment skills to assess attitudes, using a checklist or rubric assessment tool and journal methods as notes. The type of research used is descriptive research using a qualitative approach. The population in this study were all 14 teachers at SDN Kuta Vulnerable. The sample in this study were six teachers at SDN Kuta Rentang. Observation and interviews were used as data collection techniques. The data analysis method for this research uses the Miles and Huberman model. The attitude assessment plan at SDN Kuta Rentang begins with the preparation of journal tools and duplication of self-assessment and peer-assessment sheets that are made. Attitude assessment was carried out using three techniques: observation, self-assessment, and peer assessment. In addition, the results of the attitude assessment are reported in the form of a summary note of attitude observations that incorporate each indicator using the application.